2021
DOI: 10.1039/d0fo02910f
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin protects mice against 3,5-diethoxycarbonyl-1,4-dihydrocollidine-induced cholestasis

Abstract: Apigenin prevented the DDC-induced abnormal lipid metabolism, liver damage and liver fibrosis by reducing inflammation and oxidative stress. Apigenin might be a potential drug for the treatment of cholestatic liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Cell viability was detected using MTT assay [ 26 ]. After washing with PBS 3 times and incubating in DMSO (150 mL/well) for 15 min, the optical density at a wavelength of 550 nm was read by a microplate reader (BioTek Instruments, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell viability was detected using MTT assay [ 26 ]. After washing with PBS 3 times and incubating in DMSO (150 mL/well) for 15 min, the optical density at a wavelength of 550 nm was read by a microplate reader (BioTek Instruments, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted and stored at −80 °C; IL-1β and TNF-α mRNA levels were analyzed by qRT-PCR. Similarly, after extraction, total cellular proteins were stored at −20 °C and used to determine iNOS, COX-2, p38, p-p38, JNK, p-JNK, ERK, p-ERK, and SOD1 protein expression by Western blotting as described previously [ 26 ]. To analyze NF-κB translocation, RAW264.7 cells were cultured on coverslips in a 48-well plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholestasis, which is defined as the impairment of bile flow with the accumulation of toxic bile acids (BAs), is widely known as a common acute liver injury. 1,2 Cholestasis further causes serious issues, including hepatitis, cirrhosis, or even liver failure without proper treatment. 3,4 Cytotoxicity and apoptosis that are induced by toxic hydrophobic BAs are regarded as the major causes of cholestasis.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 14 ] found that Glechoma hederacea could reduce inflammation by down-regulating the expression of NF-κB and reducing the expression of α-SMA and TGF-β to inhibit fibrosis caused by cholestasis. Moreover, apigenin can inhibit DDC-induced cholestasis and fibrosis by reducing inflammation, and down-regulating the expression of TGF-β and α-SMA [ 15 ]. Bile duct transporters also play an important role in bile metabolism, and the expression of bile salt export pump (BSEP) and multidrug resistance-associated protein2 (MRP2) is closely related to the tubular transport of bile acids [ 16 ].…”
Section: Introductionmentioning
confidence: 99%